PUBLIC SERVICE PERFORMANCE OF THE POPULATION AND CIVIL REGISTRATION OFFICE OF TANGERANG DISTRICT - Grafika Hardiany Parebong; Tjahya Supriatna; Tjahjo Suprajogo (Sean Institute, 2023)
The research design used in this research is a qualitative descriptive research method. The techniques used by researchers in this research which focuses on the implementation of government programs are interviews, observation and documentation. The data analysis technique is the Miles and Huberman analysis model (2018). The results of the research show that the public service performance of the Tangerang Regency Population and Civil Registration Service is demonstrated by direct evidence, the fulfillment of appropriate and satisfactory service promises including timeliness and skill in responding to customer complaints as well as providing services fairly and accurately, the ability of officers to respond to complaints and wishes. community as the responsiveness and sense of empathy provided by Tangerang Regency Population and Civil Registration Service (Disdukcapil) officers in population administration services also shows service performance. Factors that can influence the public service performance of the Tangerang Regency Population and Civil Registration Service (Disdukcapil) include the leadership implemented, the organizational culture owned, the service standards that have been set, complaint management, control and evaluation carried out, existing facilities and infrastructure, use of information technology in providing services, and managing human resources. Efforts to improve the public service performance of the Tangerang Regency Population and Civil Registration Service (Disdukcapil) can be carried out through evaluation, improvement of facilities and infrastructure, increasing the ability of officers to provide services, training in services and the use of technology, and the introduction of population administration management in educational institutions and other institutions. to be able to maximize service.